ECOLOGICAL AUDIT IS BASIC INSTRUMENT OF ESTIMATION OF MODERN ECOLOGICAL SITUATION IN PRECARPATHIAN REGION - Міщенко, Л. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The developed method of ecological estimation of tehnogenic influence on the landscapes of ukrboecosistem and their constituents is a geological environment, relief, soils, vegetation, fauna, hydrosphere and atmosphere, there were calculated indexes which enable qualitative estimating of ecological state of all components of a landscape, making correspondent ecological maps and elaborating forecasts of environmental changes depending scenario of socio-economic development of a region, district, city, town or even an enterprise.